Family Support and Self-Efficacy in The Management of Diabetes Mellitus Among The Elderly - Faressya, Dessinnta; Hartinah, Dewi; Rahmawati, Ashri Maulida (Journal of Bionursing, 2025)
Elderly individuals with diabetes mellitus often face challenges in managing their disease, which requires a high level of self-efficacy to consistently maintain a healthy lifestyle. Self-efficacy is crucial in managing diabetes treatment among elderly patients. Family support plays a significant role in helping elderly individuals with diabetes improve their self-efficacy or confidence in performing self-care activities. The aim of this study was to determine the relationship between family support and self-efficacy in managing diabetes mellitus among the elderly at Health Center A. This research used a correlational analytic design with a cross-sectional approach. The sample consisted of 114 respondents selected through purposive sampling. The instruments used were validated and reliable questionnaires, namely the Family Support Questionnaire and the Diabetes Management Self-Efficacy Scale. Data were analyzed using the Spearman rank correlation test. The cross-tabulation results between family support and self-efficacy showed that among those who received good family support, the majority—45 respondents (69.23%)—had good self-efficacy, and half—24 respondents (50%)—had moderate self-efficacy.Meanwhile, among those who received poor family support, nearly half—20 respondents (30.77%)—had good self-efficacy, half—24 respondents (50%)—had moderate self-efficacy, and one respondent (100%) had low self-efficacy.Based on the Spearman’s rho test, a p-value of 0.024 (< 0.05) was obtained, indicating a significant relationship between family support and self-efficacy in elderly individuals managing diabetes mellitus at Health Center A in 2025.It is expected that families will continue to provide support to patients, thereby improving their self-efficacy.